Has the European Union created a healthy food environment for its citizens? Application of the Food Environment Policy Index (Food-EPI). (30th September 2020) - Djojosoeparto, S K; Kamphuis, C B M; Vandevijvere, S; Murrin, C; Stanley, I; Romaniuk, P; van Lenthe, F; Harrington, J M; Poelman, M P
Abstract: Background: European Union (EU) Member states' food environments are shaped by both national and EU policies. To date however, studies assessing food environment policies developed and set by the EU are scarce. The aim of this study was to assess the strength of EU policies to improve food environments as well as to assess the extent these policies could lead to a decrease or widening of socio-economic inequalities in dietary intake. Methods: We compiled evidence on the EU policies for each of the Food-EPI 47 indicators. A European panel of independent, non-government experts (N = 30) specialized in nutrition, obesity or chronic diseases, using the Food-EPI evidence, rated the strength of EU policies to improve food environments during an online survey in February-March 2020. The experts also rated to which extent policies could lead to a decrease or widening of socio-economic inequalities in dietary intake. In addition, experts formulated actions to improve EU food environment policies, which were prioritized during a follow-up online survey. Results: The overview of EU-level policies resulted in a 79-pages document, describing policies (or the lack thereof) for each of the 47 Food-EPI indicators. This document has been verified for completeness and accuracy by EU governmental officials. The evidence document shows that the EU has mainly binding legislation on the food labelling whereas policies on the other Food-EPI domains are mostly voluntary. Results from the online survey and the formulated prioritized actions will be presented during the conference. The results will reflect the experts' ratings supported by documented evidence and will provide meaningful guidance to EU officials and public health advocates in their efforts to improve the food environment policies set by the EU.